POLITICAL AND NATIONAL RESISTANCE IN THE KURDISH NOVELS WRITTEN IN THE MOUNTAINS (1976–1991): BASED ON MIROSLAV HROCH FRAMEWORK - Saeed, Amina; Rashid, Fouad (Humanities Journal of University of Zakho, 2025)
Kurdish novels that written in the mountains, particularly those published during the period of the Gulan Revolution (1976–1991), constitutes a critical narrative space wherein the socio-political realities of Kurdish society are represented and reimagined. These works emerge as intentional interventions by Kurdish intellectuals and writers seeking to engage in the liberation movement of Kurdistan by employing literature as a tool for political expression and national awakening. The novels serve not only as literary artifacts but as mediums for disseminating nationalist ideology and reinforcing collective identity. This study applies Miroslav Hroch theoretical framework to explore the intersection of political resistance and national identity within these novels. It investigates how textual structures and symbolic language articulate resistance, construct meaning, and challenge hegemonic discourses—particularly those that utilized religion as a mechanism for undermining Kurdish identity. In contrast, the discourse of the Kurdish political movement centered on promoting solidarity among Kurds, Arabs, Persians, and Turks, while simultaneously emphasizing national unity and cultural resilience. In the result of research contribute to the defense of the homeland through literary representation, aiming to revive cultural memory, enhance popular consciousness, and cultivate a culture of reading and national cohesion. The study further argues that these narratives function as vehicles for awakening the Kurdish national spirit, stimulating political awareness, and promoting resistance-oriented discourse as a means of social and political transformation.